2008
DOI: 10.3899/jrheum.080255
|View full text |Cite
|
Sign up to set email alerts
|

Tendinous and Ligamentous Derangements in Systemic Lupus Erythematosus

Abstract: Sacroiliitis and other tendinous and ligamentous derangements are not uncommon in patients with SLE. Based on these features and on previous reports, the term "SLE-related tendinous and ligamentous derangements" may be used to establish a common framework for further research and reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Such exclusions included diseases such as diabetes mellitus, major systemic disease, tumor, infection, back surgery, spinal fractures, and osteoporosis, in which back pain or/and sciatica is one of the complications and the intervertebral disk is prone to degeneration. [39][40][41] Moreover, the well-documented inclusion criteria were respectively applied for both asymptomatic volunteers and patients with back pain or/and sciatica. Second, the equivalence of age ranges and the balanced age distribution were achieved in the asymptomatic and symptomatic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Such exclusions included diseases such as diabetes mellitus, major systemic disease, tumor, infection, back surgery, spinal fractures, and osteoporosis, in which back pain or/and sciatica is one of the complications and the intervertebral disk is prone to degeneration. [39][40][41] Moreover, the well-documented inclusion criteria were respectively applied for both asymptomatic volunteers and patients with back pain or/and sciatica. Second, the equivalence of age ranges and the balanced age distribution were achieved in the asymptomatic and symptomatic groups.…”
Section: Discussionmentioning
confidence: 99%
“…These reports refer to abnormal changes in the atlantoaxial joint, pelvic joints and even heart valves [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al reported its presence on patients suffering from ankylosing spondylitis [11]. Additionally, Sierra-Jimenez et al , assessing the prevalence of selected clinical and radiological features of tendinous and ligamentous derangements in a consecutive sample of patients with systemic lupus erythematosus, announced that 6% of the population suffered of osteitis pubis [13]. …”
Section: Discussionmentioning
confidence: 99%